Mapping of mangrove forest at Kuala Sungai Semerak, Pasir Puteh, Kelantan Using Aerial Photograph - Zailani Maspin (Universiti Putra Malaysia Terengganu, 2014)
Mangrove forest area in Kelantan is smallest. This area is important in balancing and stabilizing the natural ecosystem as a staelter, breading ground and buffer against erosion. This forest is treater to extincetim of proper step in controlling and managing is not enforced.